2020
DOI: 10.2147/dmso.s240630
|View full text |Cite
|
Sign up to set email alerts
|

<p>Positional Vertigo and Unilateral Gradual Hearing Loss Following Sleeve Gastrectomy: A Case Report</p>

Abstract: Laparoscopic sleeve gastrectomy (LSG) is an effective treatment option in patients with morbid obesity, with rare long-term sideeffects. In this report, we present a 42-year-old woman who reported positional vertigo and unilateral gradual hearing loss plus continuous tinnitus after LSG. The patient had no signs or symptoms of mental health disorders and the results of the haematological and serum biochemical tests were normal. However, audiometric test revealed mild sensorineural hearing loss with magnitude in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The Eustachian tube malfunction brought on by muscular relaxation may explain these issues. The decrease of adipose tissue around the ear muscles may lead to muscular relaxation in and of itself [ 21 ]. A few other concerns related to complications of sleeve gastrectomy have also been studied, as it has been reported that weight loss after the surgery is linked with nutrient deficiencies too [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Eustachian tube malfunction brought on by muscular relaxation may explain these issues. The decrease of adipose tissue around the ear muscles may lead to muscular relaxation in and of itself [ 21 ]. A few other concerns related to complications of sleeve gastrectomy have also been studied, as it has been reported that weight loss after the surgery is linked with nutrient deficiencies too [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of the LVAS subjects in our study, the mean difference between binaural hearing was more than 10 dB nHL with more than half of asymmetric hearing loss rates. Individuals with asymmetric sensorineural hearing loss have reported discomfort in daily living, both audiologically and psychosocially due to poor localization of sound and poor speech recognition in noise (36)(37)(38). whether would the asymmetric hearing loss affect the development of children especially the motor development?…”
Section: -Discussionmentioning
confidence: 99%
“…7,8 Aside from the degree of inherent risk with any surgery, LSG can result in a wide range of physical and mental complications. 9 According to the American Society for Metabolic and Bariatric Surgery Clinical Issues Committee statement, the total complication rate for LSG is 0% to 24%. 10 Postoperative complications can range from chronic to potentially life-altering issues.…”
Section: Introductionmentioning
confidence: 99%